Innovative therapeutic strategies to overcome radioresistance in breast cancer - Arnold, Christoph Reinhold; Mangesius, Julian; Portnaia, Iana; Ganswindt, Ute; Wolff, Hendrik Andreas (Frontiers in Oncology, 2024)
Despite a comparatively favorable prognosis relative to other malignancies, breast cancer continues to significantly impact women's health globally, partly due to its high incidence rate. A critical factor in treatment failure is radiation resistance – the capacity of tumor cells to withstand high doses of ionizing radiation. Advancements in understanding the cellular and molecular mechanisms underlying radioresistance, coupled with enhanced characterization of radioresistant cell clones, are paving the way for the development of novel treatment modalities that hold potential for future clinical application. In the context of combating radioresistance in breast cancer, potential targets of interest include long non-coding RNAs (lncRNAs), micro RNAs (miRNAs), and their associated signaling pathways, along with other signal transduction routes amenable to pharmacological intervention. Furthermore, technical, and methodological innovations, such as the integration of hyperthermia or nanoparticles with radiotherapy, have the potential to enhance treatment responses in patients with radioresistant breast cancer. This review endeavors to provide a comprehensive survey of the current scientific landscape, focusing on novel therapeutic advancements specifically addressing radioresistant breast cancer.